Screen-Printable Functional Nanomaterials for Flexible and Wearable Single-Enzyme-Based Energy-Harvesting and Self-Powered Biosensing Devices - Veenuttranon, Kornautchaya; Kaewpradub, Kanyawee; Jeerapan, Itthipon (Nano-Micro Letters, 2023)
Developing flexible bioelectronics is essential to the realization of artificial intelligence devices and biomedical applications, such as wearables, but their potential is limited by sustainable energy supply. An enzymatic biofuel cell (BFC) is promising for power supply, but its use is limited by the challenges of incorporating multiple enzymes and rigid platforms. This paper shows the first example of screen-printable nanocomposite inks engineered for a single-enzyme-based energy-harvesting device and a self-powered biosensor driven by glucose on bioanode and biocathode. The anode ink is modified with naphthoquinone and multiwalled carbon nanotubes (MWCNTs), whereas the cathode ink is modified with Prussian blue/MWCNT hybrid before immobilizing with glucose oxidase. The flexible bioanode and the biocathode consume glucose. This BFC yields an open circuit voltage of 0.45 V and a maximum power density of 266 μW cm−2. The wearable device coupled with a wireless portable system can convert chemical energy into electric energy and detect glucose in artificial sweat. The self-powered sensor can detect glucose concentrations up to 10 mM. Common interfering substances, including lactate, uric acid, ascorbic acid, and creatinine, have no effect on this self-powered biosensor. Additionally, the device can endure multiple mechanical deformations. New advances in ink development and flexible platforms enable a wide range of applications, including on-body electronics, self-sustainable applications, and smart fabrics. Highlights: 1 Screen-printable functional nanocomposite inks are engineered for flexible, single-enzyme-based energy-harvesting, and self-powered biosensing devices. 2 A BFC powered by the same biosubstrate (glucose) is developed to harvest energy in a biofluid model and act as a self-powered electrochemical glucose. 3 Customized inks are advantageous in terms of integrating with flexible materials, which can be integrated with a wide range of wearables and soft bioelectronics.